Development of poloxamer 401 polymersomes for therapeutic proteins delivery - Cachumba, Jorge Javier Muso (2024)
In recent years, biopharmaceuticals have revolutionized the pharmaceutical sector as they present new alternatives for the treatment of intractable diseases using synthetic drugs. Although their importance is unquestionable, administration presents challenges related to immunogenicity, hypersensitivity reactions and short biological half-lives. Encapsulation in nanostructures correspond to an interesting approach that can reduce the clearance of biopharmaceuticals by increasing half-life. Among the different types of existing nanostructures, we highlight polymersomes, which present outstanding physical and chemical stability. Therefore, this work aimed at developing poloxamer 401 polymersomes for therapeutic proteins delivery. Initially, we investigated direct and indirect methods to quantify the encapsulation efficiency (%EE) of proteins in polymersomes and demonstrated that direct methods provide more reliable results and that no indirect correlation is observed between %EE and the molar mass of the proteins encapsulated. Following, the potential of polymersomes as a system for oral administration of antibodies was evaluated. IgG-FITC-loaded polymersomes were used to assess intestinal epithelial permeation in Caco-2 cell monolayers. Subsequently, an epithelial/macrophage co-culture model was used to evaluate the ability of polymersomes loaded with adalimumab, an antibody used to treat inflammatory bowel disease, in reducing the levels of pro-inflammatory cytokines (TNF-α). The results showed that IgG-FITC-loaded polymersomes increased transport across Caco-2 intestinal monolayers by 2.7-fold compared to the antibody in solution. Finally, when comparing adalimumab-loaded polymersomes, with blank polymersomes up to 5.5-fold reductions in TNF-α concentrations were observed. The results open a possibility for oral administration of biopharmaceuticals that require systemic administration. In a subsequent study, a Quality by Design approach was used to develop a spray-dried formulation of polymersomes loaded with recombinant L-asparaginase (ASNase) from D. chrysanthemi with a humanized glycosylation pattern. Fractional factorial and central rotational composite experimental designs were used to obtain the final dry formulation. In a first step, the optimized values of sucrose (180 mM) as osmolyte and ASNase (1.5 mg/mL) resulted in encapsulation efficiency (%EE) of 9.7 ± 1.8% and asparaginolytic activity of 0.297 ± 0.087 U/mL. In the next step and after optimization, 100°C inlet temperature, 3% maltodextrin DE20 as diluent, feed rate of 3.0 mL/min and atomization air flow of 750 LN/h were used to achieve a recovery yield of powder of 69 ± 2% after spray drying. In both cases, the values obtained were higher than those reported in the literature. Finally, the influence of spray drying on the cytotoxicity against leukemic cells was tested in vitro using the MTT assay and the spray-dried formulations of ASNase-loaded polymersomes presented the highest cytotoxicity (IC50 = 0.00225 ± 0.00009). Our studies demonstrated the potential of poloxamer 401 polymersomes to encapsulate therapeutic proteins and to deliver this important class of drugs.